Implementation of the Surgical Safety Checklist in Central Surgical Unit of Santo Antonius Hospital Pontianak - Dini Ivoni Chrisnawati; Saurmian Sinaga; Berlyna Saragih (Formosa Journal of Science and Technology, 2023)
Surgical Safety Checklist (SSC) is a patient safety procedure in the form of a checklist created by WHO as the basis for actions carried out by the surgical team. The aim is to find out an overview of the Implementation of the Surgical Safety Checklist. This research is quantitative descriptive observational. Checklist sheet instrument. Sample of 69 surgical patients using accidental sampling technique. The results of more than half of the implementation of SSC, namely 41 operations (59.4%) were in the poor category because the surgical team was less consistent in carrying out SSC in each phase, namely more than half of the implementation of sign-in, 39 operations (56.5%) were insufficient, the implementation of time out was 35 surgery (50.7%) was lacking and the implementation of sign out was 45 operations (65.5%) lacking. Conclusion: The implementation of the Surgical Safety Checklist in the Central Surgical Unit at Santo Antonius Hospital Pontianak is in the poor category.